Minimizing makespan of stochastic customer orders in cellular manufacturing systems with parallel machines. (January 2021) - Wu, Lang; Zhao, Yaping; Feng, Yuanyue; Niu, Ben; Xu, Xiaoyun
Highlights: Enrich cellular manufacturing literature by considering stochastic customer orders. Extend customer order production problems to stochastic multi-stage processing. Optimality properties are explored along with several important special cases. Easily implementable algorithms are constructed and shown to be effective and robust. Abstract: This study addresses a stochastic customer order production problem in cellular manufacturing systems with parallel machines. The objective is to minimize the long-run expected makespan of stochastic customer orders via proper cellular manufacturing system designs under a budget limit. Theoretical studies are conducted to explore the effect of demand uncertainty and production requirement on the optimal design and the objective. Explicit expressions are provided for dterministic workload case and several production requirement cases, which results in insights into basic principles for the optimal design to possess. Based on the theoretical analysis, three heuristic algorithms are further established. Experimental results demonstrate the effectiveness of the proposed algorithms under a variety of production scenarios. This paper extends the existing literature on customer orders by involving in stochastic arrivals and demands whose multi-stage processing is conducted in manufacturing cells. Besides, studies on design of cellular manufacturing system are enriched with the consideration of stochastic customer orders that require synchronized arrival and departure for products within an order.